Komunikasi Dalam Manajemen Sumber Daya Keluarga: Tinjauan Literatur - Pratiwi, Ismayanti; Adeni, Susri; Harahap, Machyudin Agung (UNIVED PRESS, Universitas Dehasen Bengkulu, 2025)
Family communication is a critical component in the process of Family Resource Management (FRM), which encompasses the stages of needs identification (input), planning and decision-making (process), and implementation and evaluation (output). This study aims to systematically review scholarly literature that examines the role of communication in each stage of FRM. A systematic literature review method was employed, following the PRISMA protocol, with article searches conducted via Google Scholar for publications from 2016 to 2025. A total of 17 articles met the inclusion criteria and were analyzed using thematic analysis. Findings reveal that open, empathetic, and participatory communication supports collective decision-making, conflict management, value formation, and overall family well-being. Communication also plays a significant role in the effective management of family human, financial, and emotional resources. This review underscores the importance of integrating communication into every stage of FRM and highlights the need for communication-based interventions to strengthen family resilience and well-being.